Faktor yang Berhubungan Dengan Pernikahan Dini pada Remaja Putri di Desa Nanow Kecamatan Telukdalam Tahun 2020 - Nurul Mouliza; Novi Ramini; Sriwulandari Duha (Jurusan Kebidanan Poltekkes Kemenkes Padang, 2023)
Early marriage is a marriage carried out by someone who is still at an early age or at an age that is still in their teens. The custom of arranged marriages still exists in Nias, North Sumatra. Many bridal couples do not know each other. Facts show that 36.7% of early marriages were asked by their parents and 0.9% were forced by their parents. The biggest impact of early marriage and forced marriage is exploitation and violence against women as wives in the household. The aim of this study was to determine the factors associated with early marriage for young women in Nanowa Village, Teluk District. The research design uses a quantitative method with a correlational survey approach. The population in this study were 110 young women with a sample of 52 people. Data analysis used univariate and bivariate analysis. The results of the chi-square test at a = 0.05 showed that knowledge variable was p-value 0.031 (p <0.05), economics p-value 0.000 (p <0.05), association p-value 0.005 (p<0.05), and culture-value 0.010 (p<0.05) thus showing that there is a relationship between knowledge, economy, association and culture with early marriage in adolescents. The conclusion that there is a relationship between knowledge, economy, association, and culture with marriage early childhood in young women in Nanowa Village, Telukdalam District.